Shared Representations Underlie Metaphonological Judgments and Speech Motor Control. Issue 1 (25th October 2016) - Tilsen, Sam; Cohn, Abigail C.
Abstract : Researchers often use metalinguistic judgments to investigate phonological representations. The representations are assumed to govern speech motor control and thereby shape articulatory and acoustic characteristics of speech. Yet little is known about the relationship between metalinguistic judgments, phonological representations, and motor control. This paper reports on an experiment that directly investigates the relation between metalinguistic judgments and articulatory control, hypothesizing that the two share a common representation. This hypothesis predicts that differences in judgments should be correlated with differences in the acoustic characteristics of responses. An experiment was conducted in which syllable count judgments and productions of words with tense vowel/diphthong nuclei and liquid codas were obtained from native speakers of English. A subset of these words have previously been shown to exhibit variation in syllable count judgments. Acoustic analyses of productions showed that rime durations and formant trajectories differed between words associated with monosyllabic vs. disyllabic syllable count judgments. These results support the hypothesis that a common representation is utilized by the processes responsible for metaphonological judgments of syllable count and speech motor control.